Advances in organosolv modified components occurring during the organosolv pretreatment of lignocellulosic biomass. (January 2023) - Sun, Chihe; Song, Guojie; Pan, Zhenying; Tu, Maobing; Kharaziha, Mahshid; Zhang, Xueming; Show, Pau-Loke; Sun, Fubao
Graphical abstract: Highlights: Organosolv modification is helpful to valorize the OP process. Organosolv modified products involve lignin phenolics and glycosidic compounds. Organosolv modification conforms to the lignin-first concept via group-protection. Trans-glycosylation contributes to the formation of organosolv glycosides. Co-production of modified products and hydrolysable substrates is desirable for OP. Abstract: The valorization of organosolv pretreatment (OP) is a required approach to the industrialization of the current enzyme-mediated lignocellulosic biorefinery. Recent literature has demonstrated that the solvolysis happening in the OP can modify the soluble components into value-added active compounds, namely organosolv modified lignin (OML) and organosolv modified sugars (OMSs), in addition to protecting them against excessive degradation. Among them, the OML is coincidental with the "lignin-first" strategy that should render a highly reactive lignin enriched with β -O-4 linkages and less condensed structure by organosolv grafting, which is desirable for the transformation into phenolic compounds. The OMSs are valuable glycosidic compounds mainly synthesized by trans -glycosylation, which can find potential applications in cosmetics, foods, and healthcare. Therefore, a state-of-the-art OP holds a big promise of lowering the process cost by the valorization of these active compounds. Recent advances in organosolv modified components are reviewed, and perspectives are made for addressing future challenges.